Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set - Page 477: 73


$(F+G)(5)=4$ $(F+G)(7)=3$

Work Step by Step

RECALL: $(F+G)(x) = F(x) + G(x)$ Using the rule above gives: $(F+G)(5) = F(5) +G(5)$ and $(F+G)(7)=F(7)+G(7)$ The graph shows that: $F(5)=1$; $F(7)=-1$ $G(5)=3$; $G(7)=4$ Thus, using the values above give: $(F+G)(5)=F(5) + G(5)=1+3=4$ $(F+G)(7)=F(7) + G(7) = -1+4=3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.